English Sharia Police: Gender Discrimination, and Elite Politics in Aceh - Khairul Hasni (Al-Hayat Al-Istiqomah Foundation, 2020)
The first part of this paper will argue that under Shariah Law in Aceh the Shariah Police as an agency that implements the enforcement of Islamic law based on Law No.11 / 2006 on the Government of Aceh. There are several aspects which contribute to this systematic expansion of women which will be discussed in this paper. These aspects include the fulfillment of the Wilayatul Hisbah or Shariah Police body in the contribution of the implementation of the Qanun Jinayah, and more importantly, women get justice behavior both legally and practically towards the community. The second part of the paper will explore what is or rather what should be gender discrimination in the interim of criminal law, and the number of violence was the increase from 2005 to 2019. Finally, it will discuss the possibility of overcoming these obstacles by giving greater consideration of the role of elite politic in the implementation of Shari Law in Aceh.